On the m-CAP Performance with Different Pulse Shaping Filters Parameters for Visible Light Communications - Petr Chvojka; Khald Werfli; Stanislav Zvanovec; Paul Anthony Haigh; Vaclav Hubata Vacek; Petr Dvorak; Petr Pesek; Zabih Ghassemlooy (IEEE Photonics Journal)
In pulse shaping filters, parameters such as the roll-off factor and the symbol span, which determine the overall performance, are of great importance when implementing a real-time system due to limited hardware resources. In this paper, we experimentally investigate a multiband carrier-less amplitude and phase (m-CAP) visible light communications (VLC) system employing such filters and assess the link performance for a range of filter lengths and show the relationship between the system data rate (or spectral efficiency) and computational complexity. We show that lower order m-CAP can offer the same system performance as higher order systems while offering much lower computational complexity. By optimizing the filter parameters and the order m of an m-CAP VLC link, we achieve the largest improvement in the data rate and bandwidth efficiency of 9.69% and 40.43%, respectively, when compared with 2- and 8-CAP. We also show that the m-CAP VLC link with $ m≥ 6$ can be designed with the same filter parameters to demonstrate a link with both the highest data rate and spectral efficiency simultaneously in contrast to lower order systems.